1990
DOI: 10.1177/096032719000900109
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabolism of Arsenobetaine Ingested with Fish

Abstract: 1 Six volunteers ingested 74As-labelled arsenobetaine with a fish meal. The retention and distribution of the tracer were studied by body radioactivity measurements. 2 The tracer became rapidly dispersed in soft tissues, with no major concentration in any localized organ or region. 3 In all subjects < 1% of the ingested activity remained in the body after 24 days. 4 Any losses from the skin were minor in relation to those by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
6

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 10 publications
1
34
0
6
Order By: Relevance
“…Later, one study using isotopically labeled AB showed rapid and almost complete excretion, with less than 1 % of the radioactivity remaining in the body 24 days after ingestion [48].…”
mentioning
confidence: 99%
“…Later, one study using isotopically labeled AB showed rapid and almost complete excretion, with less than 1 % of the radioactivity remaining in the body 24 days after ingestion [48].…”
mentioning
confidence: 99%
“…Seafood, including fish, shellfish, and seaweed, are important sources of organic arsenicals (arsenobetaine, arsenosugars, and arsenolipids), which are believed to have low toxicity (26)(27)(28)(29). Arsenobetaine is rapidly cleared from the blood stream and excreted unchanged via the kidneys, thereby contributing to total arsenic levels in urine (30)(31)(32). Seaweed, mollusks (e.g., scallops, mussels), and fatty fishes are rich in arsenosugars and/or arsenolipids that are metabolized into several arsenic species, including DMA, dimethylated thio arsenic species, and possibly MMA (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…Arsenobetaine is rapidly cleared from the blood stream and excreted unchanged via the kidneys, thereby contributing to total arsenic levels in urine (30)(31)(32). Seaweed, mollusks (e.g., scallops, mussels), and fatty fishes are rich in arsenosugars and/or arsenolipids that are metabolized into several arsenic species, including DMA, dimethylated thio arsenic species, and possibly MMA (30)(31)(32)(33). Therefore, in populations with moderate-tohigh fish intakes, the sum of inorganic and methylated arsenic species levels in urine cannot be used as a biomarker of iAs intake.…”
mentioning
confidence: 99%
“…On the basis of studies in Weddell seals, we have identifi ed two suitable compounds, arsenobetaine (AsB) and trimethylamine N-oxide (TMAO) (Eisert, 2003;Eisert et al, 2005). Both are specifi c to, and apparently ubiquitous in, marine prey yet are neither stored nor synthesized by higher vertebrates and in mammals are eliminated rapidly from the circulation following ingestion (Edmonds and Francesconi, 1977Yancey et al, 1982;Vahter et al, 1983;Al-Waiz et al, 1987Van Waarde, 1988;Cullen and Reimer, 1989;Brown et al, 1990;Shibata et al, 1992;Smith et al, 1994;Svensson et al, 1994;Zhang et al, 1999;Lehmann et al, 2001). The biomarker method provides information on recent food intake within a timescale of hours to days, in contrast to fatty acid signatures or stable isotopes in fl uids or tissue samples, which integrate food intake over a period of months (Iverson et al, 1997a(Iverson et al, , 1997bBrown et al, 1999).…”
Section: Monitoring Food Consumption During the Lactation Periodmentioning
confidence: 99%